2021
DOI: 10.1029/2020ea001321
|View full text |Cite
|
Sign up to set email alerts
|

NRLMSIS 2.0: A Whole‐Atmosphere Empirical Model of Temperature and Neutral Species Densities

Abstract: NRLMSIS  2.0 is an empirical atmospheric model that extends from the ground to the exobase and describes the average observed behavior of temperature, 8 species densities, and mass density via a parametric analytic formulation. The model inputs are location, day of year, time of day, solar activity, and geomagnetic activity. NRLMSIS 2.0 is a major, reformulated upgrade of the previous version, NRLMSISE-00. The model now couples thermospheric species densities to the entire column, via an effective mass profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
192
0
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 230 publications
(196 citation statements)
references
References 109 publications
2
192
0
2
Order By: Relevance
“…However, we cannot yet rule out a possibility that the NRL model overestimated the density at altitudes around 100 km. In fact, a new model of MSIS, that is, NRLMSIS 2.0 (Emmert et al., 2020), was released during the preparation of this paper. By using the python package pymsis (available at https://pypi.org/project/pymsis/), we calculated updated density profiles expected on March 26, 2016, and found that the new model gives 20%–30% lower densities at altitudes 70–110 km.…”
Section: Discussionmentioning
confidence: 99%
“…However, we cannot yet rule out a possibility that the NRL model overestimated the density at altitudes around 100 km. In fact, a new model of MSIS, that is, NRLMSIS 2.0 (Emmert et al., 2020), was released during the preparation of this paper. By using the python package pymsis (available at https://pypi.org/project/pymsis/), we calculated updated density profiles expected on March 26, 2016, and found that the new model gives 20%–30% lower densities at altitudes 70–110 km.…”
Section: Discussionmentioning
confidence: 99%
“…Data used in the development of the fieldaligned current model are available through Edwards et al (2020). The electric potential model (Edwards, 2019) was developed with the Swarm cross-track ion drift data available at https://swarm-diss.eo.esa.int/#swarm/Advanced/Plasma_Data/ 2Hz_TII_Cross-track_Dataset (Burchill and Knudsen, 2020) and Dynamics Explorer 2 Vector Electric Field measurements at https://cdaweb.gsfc.nasa.gov/pub/data/de/de2/electric_fields_vefi/ (last access: 12 January 2021, Maynard et al, 1981 Frandsen et al, 1978;Coplan et al, 1978), and data from ACE are available at https://cdaweb.gsfc.nasa.gov/pub/data/ace/mag/level_2_cdaweb/ and https://cdaweb.gsfc.nasa.gov/pub/data/ace/swepam/level_2_ cdaweb/swe_h0 (last access: August 2019, Smith et al, 1998;McComas et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…However, we cannot yet rule out a possibility that the NRL model overestimated the density at altitudes around 100 km. In fact, a new model of MSIS, i.e., NRLMSIS 2.0 (Emmert et al, 2020), was released during the preparation of this paper. By using the python package pymsis (available at https://pypi.org/project/pymsis/), we calculated updated density profiles expected on 2016-03-26, and found that the new model gives 20-30% lower densities at altitudes 70-110 km.…”
Section: Discussionmentioning
confidence: 99%